1994
DOI: 10.1093/ajcn/60.4.579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate dietary protein restriction on the progression of overt diabetic nephropathy: a 6-mo prospective study

Abstract: To assess whether moderate dietary protein restriction can delay the progression of overt diabetic nephropathy, 22 subjects with insulin-dependent diabetes mellitus were randomly assigned to an unrestricted protein diet (> 1.6 g.kg body wt-1.d-1) or a moderately protein-restricted diet (0.8 g.kg body wt-1.d-1) and followed prospectively for six mo. Direct isotope methods were used to assess renal function. Protein intake was assessed by measurement of urinary urea nitrogen. The two groups were well-matched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…High protein intakes are therefore postulated as determinants of the deterioration of clinically overt diabetic nephropathy [26] and perhaps of the progression from stages of diabetic nephropathy without clinical signs to incipient diabetic nephropathy [28,44]. However, a clear level of undesirably high protein intake has not been established for persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High protein intakes are therefore postulated as determinants of the deterioration of clinically overt diabetic nephropathy [26] and perhaps of the progression from stages of diabetic nephropathy without clinical signs to incipient diabetic nephropathy [28,44]. However, a clear level of undesirably high protein intake has not been established for persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring and adjustment of dietary protein appears particularly desirable for individuals with AER exceeding 20 individuals with normo-and microalbuminuria restriction of protein intake has been found to reduce elevated glomerular filtration rate and albuminuria independently of control of blood glucose or blood pressure [20][21][22][23][24]. The level to which protein intake should be modified in order to achieve these beneficial effects has been examined in studies conducted in individuals with miro- [21,25] and macroalbuminuria [16][17][18][19]26]. However, a uniform therapeutic approach has not yet been established and the question as to whether even normoalbuminuric individuals with diabetes should decrease or modify their current protein intake to avoid the development of renal disease remains to be clarified [27,28].…”
mentioning
confidence: 99%
“…An increasing body of evidence suggests that dietary pattern intake rather than a sole focus on individual nutrients may offer a more practical approach to dietary management of chronic diseases (122-124). (126)(127)(128)(129)(130)(131)(132)(133).Theeffectsofalow-protein (daily intake of 0.6 g protein/kg ideal body weight), low-phosphorus (500-1,000 mg/day) diet were compared with those of a control diet containing $1.0 g protein/kg ideal body weight per day and $1,000 mg phosphorus per day in 35 patients with type 1 diabetes and DKD. Study participants on the lowprotein, low-phosphorus diet had a slower rate of decline in iothalamate GFR over the course of the study.…”
Section: Sodium-glucose Cotransporter 2 Inhibitorsmentioning
confidence: 99%
“…Another study showed a decline in GFR in the low protein diet group, but did not directly compare this with the usual protein group (Dullaart RP et al 1993). Only one study (Raal FJ et al 1994) reported an increase in GFR during the low protein diet, but this increase was not significant. Zeller et al (Zeller K et al 1991) used iothalamate clearance and creatinine clearance to assess renal function.…”
Section: Macronutrients 211 Proteinmentioning
confidence: 98%
“…Of the thirteen studies that reported an association between protein and nephropathy there were three cross-sectional studies (Toeller M et al 1997;Riley MD& Dwyer T 1998;O'Hayon BE et al 2000), one case control study (Möllsten AV et al 2001), two cohort studies (Jibani MM et al 1991;Barsotti G et al 1998), six randomized controlled trials (Brouhard BH& LaGrone L 1990;Zeller K et al 1991;Dullaart RP et al 1993;Raal FJ et al 1994;Hansen HP et al 1999;Hansen HP et al 2002) and a pilot study (Percheron C et al 1995). These will be discussed in the following paragraphs by study design.…”
Section: Macronutrients 211 Proteinmentioning
confidence: 99%